Democratization and the size of government: Evidence from the long 19th century - Toke Aidt; Peter S. Jensen (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the consequences of franchise extension and ballot reform for the size of government in Western Europe between 1820 and 1913. We find that franchise extension exhibits a U-shaped association with revenue per capita and a positive association with spending per capita. Instrumental variables estimates, however, suggest that the U-shaped relationship may be non-causal and our fixed effects estimates point to substantial cross-country heterogeneity. Further, we find that the secret ballot did not matter for tax revenues per capita but might have expanded the size of government relative to GDP.
Keywords: D70; P16; 330; suffrage; threat of revolution; taxation; size of government